Growth of eel in Latvian lakes - Volkova, L.V.; Tarkach, G.M. (Baltijskij Nauchno-issledovatelskij Institut Rybnogo Khozyajstva, 1971)
Mainly large lakes - Raznas Lake (5596 ha), Usma Lake (3890 ha), Aluksnes Lake (1590 ha) were stocked with eel Anguilla anguilla in Latvia. Corresponding investigations showed that for the determination of age in eel it is necessary to account for both to its scales and otoliths. In eels of various water bodies the difference between the rings on the scales and otoliths can vary. The studies revealed that with increasing age in eel the weight increase surpasses its growth in length. It was established that in the Latvian water bodies eel has good fatness and its growth rate was comparable with eels in other countries. Published Not Known